Genomic study and lipidomic bioassay of Leeuwenhoekiella parthenopeia: A novel rare biosphere marine bacterium that inhibits tumor cell viability - Gattoni, Giuliano; de la Haba, Rafael R.; Martín, Jesús; Reyes, Fernando; Sánchez-Porro, Cristina; Feola, Antonia; Zuchegna, Candida; Guerrero-Flores, Shaday; Varcamonti, Mario; Ricca, Ezio; Selem-Mojica, Nelly; Ventosa, Antonio; et al. (Frontiers in Microbiology, 2023)
The fraction of low-abundance microbiota in the marine environment is a promising target for discovering new bioactive molecules with pharmaceutical applications. Phenomena in the ocean like diel vertical migration (DVM) and seasonal dynamic events influence the pattern of diversity of marine bacteria, conditioning the probability of isolation of uncultured bacteria. In this study, we report a new marine bacterium belonging to the rare biosphere, Leeuwenhoekiella parthenopeia sp. nov. Mr9T, isolated employing seasonal and diel sampling approaches. Its complete characterization, ecology, biosynthetic gene profiling of the whole genus Leeuwenhoekiella, and bioactivity of its extract on human cells are reported. The phylogenomic and microbial diversity studies demonstrated that this bacterium is a new and rare species, barely representing 0.0029% of the bacterial community in Mediterranean Sea metagenomes. The biosynthetic profiling of species of the genus Leeuwenhoekiella showed nine functionally related gene cluster families (GCF), none associated with pathways responsible to produce known compounds or registered patents, therefore revealing its potential to synthesize novel bioactive compounds. In vitro screenings of L. parthenopeia Mr9T showed that its total lipid content (lipidome) of the cell membrane reduces the prostatic and brain tumor cell viability with a lower effect on normal cells. The lipidome consisted of sulfobacin A, WB 3559A, WB 3559B, docosenamide, topostin B-567, and unknown compounds, therefore the bioactivity could be attributed to any of these individual compounds or due to their synergistic effect. Beyond biosynthetic potential based on genomic prediction and lipidomic bioassays, this study provides new insights into cultivation as well as the relationship between bacterial biological membrane components and their bioactivity in eukaryotic cells, encouraging to perform similar studies in other members of the rare biosphere.